Foreword - Marie Jull Sørensen (Nordic Journal of Commercial Law, 2018)
New technology – new opportunities – new challenges – new regulation? This is the common line of thought in the 10 contributions in this special issue on online intermediary platforms. The 10 contributions each provide a critical view on how online intermediary platforms fit in the context of the authors’ areas of expertise. The contributions cover overarching regulatory models and frameworks along with specific problem areas such as consumer law, labour law and tax law as well as sector specific perspectives within accommodation and finance. Last, but not least, the issue of jurisdiction is also presented. [...]